IDENTIFIKASI SEKTOR UNGGULAN KABUPATEN MINAHASA: ANALISIS DENGAN PENDEKATAN LOCATION QUOTIENT (LQ) - supriyanto supriyanto; Kaparang, Vica W.P. (CV. Denasya Smart Publisher, 2024)
This study aims to identify and analyze the leading sectors in the economy of Minahasa Regency for the 2019-2023 period using the Location Quotient (LQ) method. The data used is secondary data in the form of Gross Regional Domestic Product (GRDP) of Minahasa Regency and North Sulawesi Province obtained from the Central Bureau of Statistics. The results of the analysis show that there are several basic sectors with an LQ value> 1, namely agriculture, forestry and fisheries (LQ = 1.28), mining and quarrying (LQ = 1.28), processing industry (LQ = 1.15), electricity and gas supply (LQ = 1.18), water supply and waste management (LQ = 1.07), construction (LQ = 1.14), real estate (LQ = 1.27), and government administration (LQ = 1.21), education services (average LQ = 1. 06), and other services (average LQ = 1.06). An important finding in this study is the significant transformation in the manufacturing sector which experienced a drastic increase from LQ=0.78 in 2022 to LQ=2.56 in 2023. Meanwhile, the tourism, transportation, and information communication sectors are still classified as non-base sectors with LQ values <1. This study recommends strengthening the basic sectors through industrialization, agricultural modernization, and infrastructure development policies, as well as special programs to develop non-base sectors to create more equitable and sustainable economic growth in Minahasa Regency.